2014
DOI: 10.1002/14651858.cd011323
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral interventions for preventing breast milk transmission of HIV

Abstract: Antiretroviral prophylaxis, whether used by the HIV-infected mother or the HIV-exposed infant while breastfeeding, is efficacious in preventing mother-to-child transmission of HIV. Further research is needed regarding maternal resistance and response to subsequent antiretroviral therapy after maternal prophylaxis. An ongoing trial (IMPAACT 1077BF) compares the efficacy and safety of maternal triple antiretroviral prophylaxis versus daily infant nevirapine for prevention of mother-to-child transmission through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 64 publications
0
37
0
1
Order By: Relevance
“…The most common path of HIV infection among infants is via mother to child transmission (MTCT). 21 Infection may occur during pregnancy, labour or via the consumption of breastmilk. There are a number of factors around MTCT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common path of HIV infection among infants is via mother to child transmission (MTCT). 21 Infection may occur during pregnancy, labour or via the consumption of breastmilk. There are a number of factors around MTCT.…”
Section: Resultsmentioning
confidence: 99%
“…In developed countries HIV-infected mothers should avoid both breastfeeding and feeding EBM. 21 3.2.1.2. Cytomegalovirus (CMV).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to delivery, she said she wanted to breastfeed because, in her community, failure to breastfeed was assumed to indicate HIV infection, a recognised phenomenon known as ‘HIV by association’. This was discussed with a paediatric ID consultant, who reviewed the literature and agreed this would be reasonable. The baby was born at full term and was well.…”
Section: Case Historiesmentioning
confidence: 99%
“…HIV has been found in breast milk and the only way to guarantee that HIV will not be transmitted after birth is for complete avoidance of breastfeeding. However when this is not possible or safe, recent studies have confirmed that with the use of antiretroviral therapy to either the mother or the infant for the duration of breastfeeding, rates of transmission can be reduced [14][15][16] . This has re-ignited debate regarding the support of women especially in resource rich settings who desire to breast feed despite the availability of safe, affordable, culturally appropriate alternatives.…”
Section: Breastfeedingmentioning
confidence: 99%